Developing a business case for remanufacturing - Tan, Samantha Yanhan (2015)
Remanufacturing is a growing industry. Despite its growth in certain industries, remanufacturing is unknown to many, Some industries where remanufacturing is significant include aerospace, automotive and printing equipment. There are many drivers of remanufacturing. These drivers include environmental, social, legislative and economic drivers. While these drivers lead to growth in remanufacturing, there are significant barriers to remanufacturing that have yet to been address. To develop a business case for remanufacturing, industries have to be studied to understand the extent and the parts that are commonly remanufactured. Business models relevant to remanufacturing will also be discussed to identify the attributes and the key drivers of these business models. Case studies of some remanufacturing firms will be discussed to assist in the understanding of how these business models are applied in reality.